Inborn or acquired changes in children under three years of age – a review of the literature - Kapel-Reguła, Aleksandra; Radwan-Oczko, Małgorzata (Journal of Education, Health and Sport, 2022)
This study aimed to discuss some inborn and acquired changes in the oral cavity in young children under three years of age. Based on current literature, eruption cyst, Riga-Fede disease, natal and neonatal teeth, congenital epulis, Epstein pearls, Bohn’s nodules, and gingival cyst of the newborns have been described. The symptoms, clinical presentation, and histological features of these changes, their epidemiology, prevalence, etiopathogenesis, differential diagnosis, and management were taken into consideration to present them accurately. Described oral normal findings and anomalies are not very common, so they require precise diagnosis and management properly. Having relevant knowledge on issues is important both for the pediatricians and pediatric dentists who always cooperate to distinguish the pathology or anomaly and start dealing with it. To our knowledge, this is the first literature review presenting comprehensive and thorough specification of abnormalities occurring in children’s mouth, basing on the most recent scientific literature between 1999 and 2022.